Analisis Penerapan Biaya Kualitas Untuk Meningkatkan Efisiensi Produksi Pada Baker’s Queen Sekayu - Romanda, Candra (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2019)
The purpose of this study was to determine the application of quality costs to improveproduction efficiency at Baker’s Queen Sekayu. The data used in this study are primary data andsecondary data. Data collection techniques in this research are documents, interviews and literaturestudy. The data analysis technique in this study is a quantitative analysis technique. Quality costsincurred in the company amounted to 5.88% of total sales. From the analysis that has been done thatthe cost of quality occurs inefficiency of 3.38% because it exceeds the existing standard of 2.5%. socompanies need to take action to reduce the cost of quality in the company by increasing preventioncosts to reduce the cost of failure needed to increase control costs (prevention costs and assessmentcosts), so this can increase the effectiveness of quality control activities to improve productionefficiency.Keywords: Quality, Cost of Quality, control, failure, Efficiency